Double Aneuploidy - A Rare Condition : Report of Two Cases (Journal of Bangladesh College of Physicians and Surgeons, 2015)
The chance of two chromosome abnormalities occurring in one conceptus is rare. Here we report two cases of double aneuploidy with karyotype 48,XYY,+21 and 48,XXY,+21.The diagnosis was confirmed by cytogenetic analysis using peripheral blood followed by Giemsa banding technique. Clinically both the children had most of the phenotypic features of Trisomy 21. However phenotypic features of XYY were not present but the child with XXY had undescended right testis .The purpose of this communication is to report such rare disorders discovered as the result of the evaluation for Trisomy 21.J Bangladesh Coll Phys Surg 2014; 32: 171-173